Development of the Diabetes Injection Device Experience Questionnaire (DID-EQ) and Diabetes Injection Device Preference Questionnaire (DID-PQ) - Louis S. Matza; Kristina S. Boye; Katie D. Stewart; Rosirene Paczkowski; Jessica Jordan; Lindsey T. Murray (SpringerOpen, 2018)
Abstract Background Previous research has examined patient perceptions of insulin injection devices. However, injectable medications other than insulin are increasingly used to treat type 2 diabetes, including GLP-1 receptor agonists. No patient-reported outcome (PRO) instruments have been developed taking into account the experiences of patients using newer injection devices, which are often different from devices used for insulin. Therefore, the purpose of this qualitative study was to develop two draft PRO instruments focusing on patients' experiences with these newer injection devices (one instrument assessing perceptions of a single injection device, and another assessing preferences between two devices). Methods Questionnaire development proceeded in six steps: literature review, interviews with six device experts, concept elicitation interviews with patients (N = 32), preliminary translatability assessment, cognitive interviews with patients (N = 20), and final translatability assessment. Results Literature review and expert interviews were conducted to inform a concept elicitation interview guide. In concept elicitation in the US, UK, and Germany, patients with type 2 diabetes reported a range of injection features that influenced their perceptions of non-insulin injection devices (e.g., requirements for preparation of the medication/device, issues related to the needle, ease-of-use, portability). Two draft "item pools" were developed based on the literature review, expert interviews, and concept elicitation results. In cognitive interviews, patients recommended minor revisions and indicated that the draft instruments were generally clear, comprehensible, and relevant to their experience with non-insulin injectable medication. The instruments were refined based on the cognitive interviews and translatability assessment, resulting in two questionnaires. Conclusions The various steps of qualitative research support the content validity of these new PRO instruments, which are the first developed specifically to assess perceptions of non-insulin injection delivery systems. Despite some overlap with insulin-focused questionnaires, the new instruments are distinct from previous instruments (omitting content that would not be relevant to patients receiving non-insulin injectable treatment, while including content that is not included in the insulin focused instruments). This qualitative research yielded two draft questionnaires that are grounded in patient perceptions and ready for psychometric validation studies with larger samples of patients with type 2 diabetes.